THE INTERACTION OF DIGITAL LIFESTYLE ON MILLENNIAL ECONOMIC DEVELOPMENT IN LIMA PULUH KOTA REGENCY - Mirsal (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The development of digital technology has shaped new lifestyles among the millennial generation, which directly affect the dynamics of regional economic development. Digital lifestyles not only influence consumption patterns but also encourage the emergence of productive economic activities based on technology. This study aims to analyze the interaction between digital lifestyles and the economic development of the millennial generation in Lima Puluh Kota Regency. The research adopts a descriptive qualitative approach using a literature review method. Data were obtained from national scientific journals, conference proceedings, and academic books relevant to the digital economy, digital lifestyles, and the millennial generation. The results indicate that the digital lifestyle of the millennial generation contributes positively to regional economic development through the growth of digital entrepreneurship, the utilization of e-commerce, and the strengthening of locally based creative economies. However, challenges such as limited digital infrastructure and low levels of digital literacy remain major obstacles.